Myocardial T1 mapping and extracellular volume quantification: an overview of technical and biological confounders - Piechnik, S; Jerosch-Herold, M (Springer, 2017)
Novel tissue biomarkers based on the spin-lattice relaxation time T1, a fundamental property in the theory of magnetic resonance physics, have emerged as a new approach for myocardial tissue characterization with many validated clinical applications. This article is intended as an overview of the physical and physiological mechanisms underlying the interpretation and the accuracy of any practical measurement of T1, or derived biomarkers such as extravascular volume fraction, and also includes a discussion of potential pitfalls. Numerous caveats und knowledge gaps related to the precise interpretation of T1-based biomarkers remain, which are being addressed incrementally through ongoing research. Equally important, further careful standardization will pave the way for a wider clinical translation of these novel T1-based biomarkers of tissue remodeling, which have been well validated for their sensitivity to pathophysiological changes, though for the most part in single-center studies.